Downregulation of MYO1C mediated by cepharanthine inhibits autophagosome-lysosome fusion through blockade of the F-actin network - Yanhao Zhang (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background MYO1C, an actin-based motor protein, is involved in the late stages of autophagosome maturation and fusion with the lysosome. The molecular mechanism by which MYO1C regulates autophagosome-lysosome fusion remains largely unclear. Methods Western blotting was used to determine the expression of autophagy-related proteins. Transmission electron microscopy (TEM) was used to observe the ultrastructural changes. An immunoprecipitation assay was utilized to detect protein-protein interactions. Immunofluorescence analysis was used to detect autophagosome-lysosome fusion and colocalization of autophagy-related molecules. An overexpression plasmid or siRNA against MYO1C were sequentially introduced into human breast cancer MDA-MB-231 cells. Results We show here that cepharanthine (CEP), a novel autophagy inhibitor, inhibited autophagy/mitophagy through blockage of autophagosome-lysosome fusion in human breast cancer cells. Mechanistically, we found for the first time that MYO1C was downregulated by CEP treatment. Furthermore, the interaction/colocalization of MYO1C and F-actin with either LC3 or LAMP1 was inhibited by CEP treatment. Knockdown of MYO1C further decreased the interaction/colocalization of MYO1C and F-actin with either LC3 or LAMP1 inhibited by CEP treatment, leading to blockade of autophagosome-lysosome fusion. In contrast, overexpression of MYO1C significantly restored the interaction/colocalization of MYO1C and F-actin with either LC3 or LAMP1 inhibited by CEP treatment. Conclusion These findings highlight a key role of MYO1C in the regulation of autophagosome-lysosome fusion through F-actin remodeling. Our findings also suggest that CEP could potentially be further developed as a novel autophagy/mitophagy inhibitor, and a combination of CEP with classic chemotherapeutic drugs could become a promising treatment for breast cancer.